"Strathclyde". A residential district, Barbados, B. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This photo shows a view of Strathclyde, a residential area in Barbados. Both sides of the street are lined with palm and other trees and houses. Each house is separated by a wall. This is a divided back postcard. Back of the Postcard: NP £9 (Handwritten in pencil) Published by Knights Ltd., Barbados. Printed in Saxony.
Landscape; Black & white; 3 ½ x 5 ½ "
Keywords: Architecture; Residential Streets; Neighborhoods; Houses; Architectural elements; Trees